Non-contact and non-destructive detection and identification of Bacillus anthracis inside paper envelopes. (August 2019) - Kendler, Shai; Aharoni, Ran; Cohen, Shay; Raich, Raviv; Weiss, Shay; Levy, Haim; Mano, Ziv; Fishbain, Barak; Ron, Izhar
Highlights: Proof-of-concept for the identification of concealed BAS using SWIR-HSI is presented. Identification is based on removal of the envelope signal using an automatic algorithm. This technology may be used as a fast scanner prior to classical bioanalytical methods. Abstract: Efficient and safe detection of Bacillus anthracis spores (BAS) is a challenging task especially in bio-terror scenarios where the agent is concealed. We provide a proof-of-concept for the identification of concealed BAS inside mail envelopes using short-wave infrared hyperspectral imaging (SWIR-HSI). The spores and two other benign materials are identified according to their typical absorption spectrum. The identification process is based on the removal of the envelope signal using a new automatic new algorithm. This method may serve as a fast screening tool prior to using classical bioanalytical techniques.